2023
DOI: 10.3389/fpubh.2023.1072115
|View full text |Cite
|
Sign up to set email alerts
|

Depression and oral health-related quality of life: A longitudinal study

Abstract: ObjectivesGeriatric oral health-related quality of life is a relatively new but rapidly growing concept as it is directly related to the general wellbeing and self-esteem of older adults. This study assessed the impact of worsening depression symptoms on oral health-related quality of life using representative nationwide data of Korean older adults.MethodsThis study comprised a longitudinal sample of older adults aged ≥60 from the Korean Longitudinal Study of Aging (2016–2020). After applying the exclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…First, the worse OHRQoL of these patients needs discussion. The available literature on patients with affective disorders supports the results of the current study, as they show a reduced OHRQoL in those individuals [7][8][9][10][11]. A study on the Japanese elderly showed that depressive symptoms were associated with a more than five-fold higher risk of impaired OHRQoL [12].…”
Section: Ohrqol Disparities In Patients With Depressive Disorders And...supporting
confidence: 87%
See 2 more Smart Citations
“…First, the worse OHRQoL of these patients needs discussion. The available literature on patients with affective disorders supports the results of the current study, as they show a reduced OHRQoL in those individuals [7][8][9][10][11]. A study on the Japanese elderly showed that depressive symptoms were associated with a more than five-fold higher risk of impaired OHRQoL [12].…”
Section: Ohrqol Disparities In Patients With Depressive Disorders And...supporting
confidence: 87%
“…A study on the Japanese elderly showed that depressive symptoms were associated with a more than five-fold higher risk of impaired OHRQoL [12]. Another longitudinal study showed that an exacerbation of depression would be negatively associated with OHRQoL in the elderly [9]. However, the available literature consists of heterogeneous samples, whereby specific cohorts like elderly individuals or substance users were often included.…”
Section: Ohrqol Disparities In Patients With Depressive Disorders And...mentioning
confidence: 99%
See 1 more Smart Citation
“…OHRQoL can have a range of negative impacts on the physical and mental health, social relationships, and well-being of older adults [ 37 ]. OHRQoL in older adults is influenced by a variety of factors, including oral health indicators, general health status, sociodemographic status (gender as female and age), and economic status [ 35 , 38 , 39 ]. There is a clear need to identify risk factors for poor OHRQoL in older adults and to develop interventions based on these factors.…”
Section: Discussionmentioning
confidence: 99%